A Bis‐Sulfonyl O, C, O Aryl Pincer Ligand and its Tin(II) Complex: Synthesis, Structural Studies, and DFT Calculations1. Issue 3 (27th November 2014) - El Ezzi, Mohammad; Lenk, Romaric; Madec, David; Sotiropoulos, Jean‐Marc; Mallet‐Ladeira, Sonia; Castel, Annie
Abstract The efficiency of the deprotonated aryl bis‐sulfone [2, 6‐{(p‐tolyl)SO2}2C6H3]− as an O, C, O‐coordinating pincer‐type ligand was described. The bis‐sulfone precursor was synthesized using a straightforward palladium‐catalyzed cross‐coupling reaction. As a result of directed ortho metalation (DoM) through sulfonyl groups, a selective lithiation of the aryl group was achieved and the corresponding carbanion was isolated and its structure determined by single‐crystal X‐ray diffraction analysis. A heteroleptic tin(II) complex has been prepared by a nucleophilic substitution reaction. Crystallographic analysis and DFT calculations indicate that the bis‐sulfonyl moiety acts as a new O, C, O‐coordinating pincer‐type ligand with intramolecular SO coordination to a tin(II) center. The cis form with the two nonbonded oxygen atoms of the sulfonyl groups on the same side is preferentially obtained.